1999
DOI: 10.1097/00001756-199904260-00009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inner ear fluid in the rat by vasopressin

Abstract: The anti-diuretic hormone vasopressin has been shown to be important in regulating inner ear fluid. The diuretic hormone, CNP, and its receptor, ANP-B receptor, may also function in the regulation of inner ear fluid. To determine whether vasopressin directly affects the fluid level, we infused this hormone to rat and assay of V2-AVP receptor mRNA by semiquantitative RT-PCR demonstrated a significantly lower level of this transcript in vasopressin-infused animals than in saline-infused animals. The levels of CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 4 publications
4
31
0
1
Order By: Relevance
“…Previous studies have shown that AQP2 protein and/or mRNA are expressed in the inner ear of rats. 19,39,46 Furthermore, the V2 receptor and/or its mRNA are found in the cochlea. 16,18 These previous studies suggest that water homeostasis in the inner ear is partly regulated via the VP-AQP2 system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that AQP2 protein and/or mRNA are expressed in the inner ear of rats. 19,39,46 Furthermore, the V2 receptor and/or its mRNA are found in the cochlea. 16,18 These previous studies suggest that water homeostasis in the inner ear is partly regulated via the VP-AQP2 system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the following evidence has accumulated to suggest that VP is closely associated with the formation of EH: (1) plasma levels of arginine VP are higher in patients with MD and may depend on the phase that the patient is in, [9][10][11] (2) acute and chronic application of arginine VP produces EH in guinea-pigs and rats, [12][13][14] (3) V2 receptor mRNA is expressed in rat and human inner ear, [15][16][17][18] and (4) expression of V2 receptor mRNA in the rat inner ear is downregulated by VP application. 19 Such accumulated evidence has led to the assumption that production of endolymph is controlled by VP-AQP2 system.…”
mentioning
confidence: 99%
“…We therefore sought to determine whether vasopressin can directly induce endolymphatic hydrops in the rat inner ear. In the previous study, we found that infusion of vasopressin induced a down-regulation of V2 AVP receptor mRNA in these cases [6]. These findings suggest that vasopressin directly regulates fluid levels in the inner ear, most likely by a down-regulation of its receptor.…”
Section: Discussionmentioning
confidence: 67%
“…The results of the assay of renal-type arginine vasopressin (V2-AVP) receptor mRNA by quantitative RT-PCR demonstrated a significantly lower level of this transcript in vasopressininfused rats than in saline-infused rats. The levels of CNP and ANP-B receptors mRNA, however, were the same in both groups of rats [6].…”
Section: Introductionmentioning
confidence: 79%
“…Sawada et al [13] and Beitz et al [9] have shown respectively AQP2 mRNA in the rat cochlea and endolymphatic sac with RT-PCR, a quantitative analysis but not a localization detection. Though all these data were based upon rat or mouse with some discrepancies, they suggest that AQP2 may play important roles in regulation of endolymph by vasopressin because vasopressin receptor in the inner ear has been identified [14,15], and regulation of AQP2 expression by vasopressin via their receptors and its affect on electrolytes metabolism has been well established in kidney [1,5].…”
Section: Discussionmentioning
confidence: 99%